KESETARAAN GENDER PERSPEKTIF ISLAM DAN KRISTEN: Kesetaraan Gender Perspektif Islam dan Kristen (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2024)
Until now, gender equality is still an interesting issue to discuss, because most people, especially those living in various regions of Indonesia, still misunderstand gender equality. They think that gender equality is an action to unite women, even though the gender equality movement is to demand justice so that there is no discrimination for women, both in the fields of education, law, social and economic matters. The differences in the biological anatomy of men and women are a decree from God which still has several problems, both in terms of the substance of events and the roles they play in society. In fact, all religions without exception view all of His creation as equally good creatures in the eyes of the Creator, so they do not deserve to be treated in a discriminatory manner. The aim of this research is to further find out how gender equality is from the perspective of two religions, namely Islam and Christianity, using qualitative research and literature study methods. For technical data collection by collecting data, reducing data, analyzing data, drawing conclusions. In this research the author found that Islam views women as equal and even glorifies them. This is stated in the holy book Al-Qur’an and also the Prophet’s treatment of women who gave them their rights after the arrival of Islam on earth. Similar to Islam, Christianity holds the view that Allah differentiates between human genders but does not differentiate roles between the two, all of them are equal before the Creator.